Impact of Corticosteroid-Free Regimen on Interstitial Fibrosis Following Kidney Transplantation - Simon Ville; Karine Renaudin; Lionel Rostaing; Morgane Pere; Nassim Kamar; Christophe Legendre; Emmanuel Morelon; Elisabeth Cassuto-Viguier; Christophe Mariat; Antoine Durrbach; Matthias Buchler; Laure-Hélène Noel; et al. (Kidney International Reports)
Introduction: In kidney transplantation, concerns remain about whether corticosteroids (CS) avoidance could favor interstitial fibrosis (IF) and its progression. We conducted a multicenter randomized noninferiority clinical trial to evaluate the histopathological progression of IF using an innovative automated method in patients receiving CS or not. Methods: Low immunological risk recipients of a kidney allograft for whom an analyzable biopsy was available at implantation were randomly assigned to receive a CS-free regimen (CS−) or a standard CS tapering regimen (CS+). All patients received induction therapy with basiliximab, and conventional maintenance therapy. The primary outcome was the difference in the percentage change of IF between the baseline and the 1-year protocol biopsy with a prespecified 10% noninferiority margin. Results: A total of 108 patients were analyzed in the full analysis set (FAS) population as follows: 52 patients in the CS+ group and 56 patients in the CS− group. Complete avoidance of CS was reached in 36 (64%) CS− patients (per-protocol [PP] population). In the FAS population, the mean percentage of IF at implantation was 19.5% ± 7.9% in the CS− group (n = 51) and 17.9% ± 7.8% in the CS+ group (n = 49; P = 0.3), and 25.9% ± 11% (n = 43) and 21.5% ± 11.2% (n = 39; P = 0.03) at 1 year. Considering the difference in IF change, the CS− group was noninferior to the CS+ group neither in the FAS and PP population: 4.45% 95% confidence interval [CI]: [−0.4% to 9.3%] and 3.0% 95% CI: [−2.7% to 8.6%], respectively. Conclusion: Progression of IF during the first year following kidney transplantation was not inferior among patients without CS compared with patients with CS.